Preprocess Sonication Maintains Quality and Inhibits Browning of Fresh-cut Fruit Using Apples as the Fruit Model - Pathitta Thuamsuk; Sirima Sinthusamran; Chairat Techavithiporn; Suriyan Supapvanich (Current Applied Science and Technology, 2024)
Ultrasonic (US) waves (sound waves) have been used to preserve and improve the quality of fresh fruits and vegetables. The goal of this study was to determine whether pre-process US treatment was useful in reducing browning and retaining certain aspects of fresh-cut ‘Gala’ apples’ quality. The apples were sonicated at a frequency of 120 kHz for 0, 5, 10 and 15 min before processing and then the processed apples were stored at 4±1°C. The US treatment at 5 min significantly delayed the loss of lightness, and increases in colour difference and browning index, and maintained whiteness compared to other treatments. The US treatment at 5 min controlled enzymatic browning reaction, probably due to inhibition of polyphenol oxidase activity. US treatments could delay the loss of hardness compared to the control treatment but had no influence on the total soluble solids content. Interestingly, US treatments induced antioxidant activity in fresh-cut apples during storage. In summary, the 5 min sonication could prevent browning and enhance the quality of fresh-cut apples during storage.
Keywords: Postharvest Quality and Shelf Life Management; Plant Physiology and Cultivation Studies; Nanocomposite Films for Food Packaging